Les infinitives problématiques : l’exemple de cease to - Geneviève Girard-Gillet (Anglophonia, 2008)
Infinitives are usually thought to refer to future events relative to the time denoted by the matrix verb they depend on. But with some verbs this temporal interpretation turns out to be false. “Cease” is one of these verbs which raise questions, as the process expressed by the non-finite form has necessarily occurred before its cessation. Still more surprising is that “cease” elicits another complementation, namely a gerundive. This article aims to show that analyses of to-infinitives have to take into account the existence of this verb if any kind of generalization is to be reached. We draw on a semantic/syntactic notion developed by research in Generative Grammar, the notion of unaccusativity to explain some phenomena. Some verbs appearing in the complementation of “cease” have two interpretations: an unaccusative one and an agentive one. The former is realized via the infinitive and the latter via the gerundive.